Modelling the kinetics of peroxidase inactivation and colour changes of seedless guava (Psidium guajava L.) during thermal treatments - Ganjloo, Ali; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; Bimakr, Mandana (IDOSI Publications, 2009)
The kinetics of thermal inactivation of peroxidase and colour changes in seedless guava (Psidium guajava L.) due to hot water blanching were studied in the temperature range of 80-95°C. Peroxidase inactivation kinetics followed a first-order Arrhenius model, where the activation energy and rate of the reaction at a reference temperature of 87.5°C were 101.27±3 kJ mol-1 and 0.023±4×10-3s-1, respectively. Colour was quantified using the L, a, b in Hunter system. The results indicated that colour system parameters (L, a, b) followed a first-order Arrhenius kinetics model with activation energies (Ea) of 120.43±3, 86.45±5 and a 100.03±2, kJmol-1, respectively. The zero-order kinetic model was applied to total colour difference (TCD) resulting in activation energies of 111.65±5 kJmol-1. Good agreement was found between estimated and experimental data in all cases (R2>0.91).